2019
DOI: 10.3390/ijms20174118
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cardiovascular Function in Primary Hypertension in Rat by SKA-31, an Activator of KCa2.x and KCa3.1 Channels

Abstract: The aim of this study was to investigate the hemodynamic effects of SKA-31, an activator of the small (KCa2.x) and intermediate (KCa3.1) conductance calcium-activated potassium channels, and to evaluate its influence on endothelium-derived hyperpolarization (EDH)-KCa2.3/KCa3.1 type relaxation in isolated endothelium-intact small mesenteric arteries (sMAs) from spontaneously hypertensive rats (SHRs). Functional in vivo and in vitro experiments were performed on SHRs or their normotensive controls, Wistar-Kyoto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
(127 reference statements)
1
6
0
Order By: Relevance
“…In the mesenteric G3 artery, a greater (about 20%) significance of NO-mediated vasorelaxation in WKY rats and SHR than in DOCA-salt rats was determined. Like in our previous studies, vasodilator prostanoids play a small but constant role in modulating vascular tone independent of the vessel size, especially in normotensive rats [40,41].…”
Section: Vascular Changes Related To Hypertensionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the mesenteric G3 artery, a greater (about 20%) significance of NO-mediated vasorelaxation in WKY rats and SHR than in DOCA-salt rats was determined. Like in our previous studies, vasodilator prostanoids play a small but constant role in modulating vascular tone independent of the vessel size, especially in normotensive rats [40,41].…”
Section: Vascular Changes Related To Hypertensionsupporting
confidence: 81%
“…Additionally, we evaluated the expression of the mRNAs of KCNN4 and KCNN3, whose products (the intermediate and small calcium-activated potassium channels K Ca 3.1 and K Ca 2.3, respectively) are thought to mediate endothelium-dependent hyperpolarization (EDH). They play a pivotal role in NO-/PGI 2 -independent endothelium-mediated vasorelaxation in resistance vessels and act as a backup system to maintain endothelial function in situations associated with decreased bioactivity of NO-e.g., in hypertension [40]. We revealed changes dependent on the hypertension model, since both KCNN4 and KCNN3 were downregulated in the aortas and mesenteric G3 arteries of SHR, whereas their expression levels were unchanged in DOCA-salt rats, with the exception of the KCNN4 level being enhanced in aortas.…”
Section: Vascular Changes Related To Hypertensionmentioning
confidence: 84%
“…For immunohistochemical analysis, the EnVision method was used according to Kloza et al [ 55 ], using antibodies against von Willebrand factor (vWF) (1:2000, 2 h incubation at room temperature (RT), Polyclonal Rabbit Anti-Human (no cat. A 0082); DakoCytomation, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“… 28 NO, synthesized by eNOS, is an endothelial-derived vasodilator, that maintains microvascular endothelial physiological function via the nitrate–nitrite–NO pathway. 29 It has been reported that the reduction 30 and inactivation 31 of eNOS in hypertensive rats might mediate vasodilatory dysfunction. Consistently, the present study showed a reduction in the amplitudes of NO-independent and NO-dependent endothelial oscillators, together with increased nitrate/nitrite and endothelin-1 levels in SHRs, which may result in a decrease in flow-mediated vasodilation.…”
Section: Discussionmentioning
confidence: 99%